Genetic parameter analysis and evaluation of maize hybrids under local climatic condition of Mymensingh, Bangladesh - Nahid Hasan; Md. Jahid Hasan Jone; Biswajit Das; Md. Nure Adil Siddique; Yousuf Islam; Md. Abul Kashem (Heliyon)
Maize is a cornerstone of global agriculture, essential for food security, livestock feed, and industrial uses. With the increasing demand for maize due to population growth and changing dietary patterns, there is a pressing need to enhance maize production. Hybridization is a strategic approach for developing high-yielding and stress-tolerant maize varieties and evaluating these hybrids in specific environmental conditions is vital for optimizing yield and adaptability. With this objective, a field experiment was conducted to evaluate the growth and yield performance of ten hybrid maize varieties under the local climatic conditions of Mymensingh. A randomized complete block design with three replicates was used to collect data on thirteen different parameters. Significant variation was observed among the hybrids for all phenological, growth, and yield contributing traits. The phenotypic coefficient of variation exceeds the genotypic coefficient of variation, indicating substantial environmental interactions. Heritability estimates ranged from 59% to 98%. Positive correlations were noted between cob length, cob diameter, grains per row, and 100-seed weight with kernel weight per plant. Path coefficient analysis revealed that plant height, cob diameter, number of leaves at harvest, cob length, and grains per row positively influenced grain yield. Among the hybrids, Kaveri54 exhibited superior performance with a kernel weight of 202.7 g. Therefore, Kaveri54 is recommended as a promising hybrid for maize cultivation in the Mymensingh region, which will support future breeding efforts aimed at improving yield and resilience.